Residential cognitive–behavioral therapy versus therapeutic community for patients with methamphetamine use disorders in the Philippines: A randomized controlled trial - Takayuki Harada; Tomohiro Shirasaka; Toshiaki Baba; Aya Mizusawa; Alfonso Villaroman; Rosalina Noguera-Caoile; Ma. Alodia Mercado; Jasmin Peralta; Keigo Hatto; Shogo Kanamori (Addictive Behaviors Reports)
Introduction: In the Philippines, an estimated 1.8 million people use methamphetamine. Despite the government’s anti-drug campaign, repressive methods have been ineffective. Thus, treatment and human services are needed. We developed a cognitive–behavioral therapy (CBT) program for residential and rehabilitation center-based treatment and examined its effectiveness. Methods: In this block-randomized single-blinded trial, control group participants received therapeutic community-type treatment only, while the intervention group additionally participated in our CBT program for 6 months. Primary outcomes were methamphetamine re-use, measured by urine tests and self-report at 3-months post-discharge, and self-reported well-being at pre-discharge and 3-months post-discharge. Findings: Participants (n = 326) were randomized into intervention (n = 162) and control (n = 164) groups. At follow-up, 3/27 (11.11 %) and 1/27 (3.70 %) participants in the respective groups had positive urine tests for drug re-use (χ2(1) = 1.08, n.s., r = 0.037, 95 %CI [-0.064, 0.212]). The self-reported drug re-use rate was significantly higher in the intervention group (χ2(1) = 9.18, p < 0.01, r = 0.14 (95 %CI [0.050, 0.231]). However, pre-discharge self-rated health (F(1, 311) = 6.32, p < 0.025, η2 = 0.02, 95 %CI [0.001, 0.06]) and problem-focused coping (F(1, 311) = 6.50, p < 0.025, η2 = 0.021, 95 %CI [0.001, 0.06]) were significantly better among intervention group participants than among control participants. Conclusions: Although without significant effect on drug re-use, the intervention had a small positive effect on patients’ well-being, coping skills, and other psychological variables. Additional research is required to develop effective treatments for methamphetamine use in this region.